(untitled) (Kronika Bydgoska, 2010)
The ZOO Polish Fauna Garden in Bydgoszcz is located in the Forest Culture and Leisure Park (LPKiW) in 173 Gdańska Street. Covering 830 ha, this is the largest Polish municipal park. The plan to establish a zoo in Bydgoszcz was madę already in 1975, whereas officially it was opened in July 1978. At first, it covered 6 ha and presented 40 animal species. Currently, the zoo has about42 mammal species, 73 bird species, 15 reptile species, 10 amphibian species, and 2 invertebrate species. The ZOO is one of smaller zoological gardens in Poland (13th as regards the number of animal species), covering 14 ha. The garden gradually gained successive animal species. The first ones were Polish ponieś, roe deer, pheasants, peacock pigeons and pouters. Next, an artificial pond was constructed for free waterfowl (1979). Later, brown bears (1984), lynx, wildcats, wood grouses and beavers (1986), elk (1999), and chamoises (2001) were brought to the zoo. Since the beginning, the zoo has been specialised in exhibition and breeding of native fauna. In 2004, such exotic animal species as suricates, wallabies, coatis (southem coati), macaąues, ring-tailed lemurs, zebras, parrots, emus and ostriches appeared in the zoo. Since 2005, visitors have had an opportunity to observe rodents, reptiles and amphibians. The Polish Fauna Garden conducts also education activities for children and adults.